1998
DOI: 10.1038/sj.leu.2401065
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival with early intensification: combined results from the Medical Research Council childhood ALL randomised trials, UKALL X and UKALL XI

Abstract: The Medical Research Council (MRC) United Kingdom trial for childhood acute lymphoblastic leukaemia (UKALL X) randomised patients aged 0-14 years inclusive with an initial white blood count of less than 100 × 10 9 /l to receive an early intensification block, a late intensification block, both, or neither. The next trial, UKALL XI, for children aged 1-14 years, randomised between different central nervous system (CNS) directed therapies. At the beginning of the trial, all patients were also randomised between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 15 publications
0
43
0
Order By: Relevance
“…33,34 Potential reasons for these neurotoxicities have been reviewed in a previous publication, 34 Overall outcome data from this clinical trial compare favorably with previous POG trials and those of other groups treating children for HR-ALL (62-75%). [9][10][11][12][13][14][15][16][17][18][19][20] Because risk group criteria differ among large cooperative groups treating childhood ALL, external comparisons are difficult and hazardous. However, 66% of the patients in this study would be considered high risk by the CTEP/NCI consensus risk group definition (age у10 years, or WBC у50 000) thus adding some validity to cross comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 Potential reasons for these neurotoxicities have been reviewed in a previous publication, 34 Overall outcome data from this clinical trial compare favorably with previous POG trials and those of other groups treating children for HR-ALL (62-75%). [9][10][11][12][13][14][15][16][17][18][19][20] Because risk group criteria differ among large cooperative groups treating childhood ALL, external comparisons are difficult and hazardous. However, 66% of the patients in this study would be considered high risk by the CTEP/NCI consensus risk group definition (age у10 years, or WBC у50 000) thus adding some validity to cross comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20] Increased toxicity was also noted with the aggressive use of myelosuppressive agents. 9,13,14,16,18,[19][20][21][22] However, preliminary results from POG 8698 suggested that early intensification with the less toxic combination of intermediate-dose methotrexate (MTX) and mercaptopurine (MP) might be as effective as the more myelosuppressive combinations used in another POG pilot study (POG 8398) for HR-ALL. 13,17 In 1991, the POG opened a group-wide randomized phase III clinical trial (POG 9006) to treat children with HR-ALL.…”
Section: Introductionmentioning
confidence: 99%
“…The primary diagnosis of leukaemia was made at 3.8 (0.85–15.0) years and 5.6 (1.6–14.1) years of age in the HSCT-TBI survivors and chemotherapy-only survivors, respectively. All subjects were treated according to contemporaneous UK national paediatric leukaemia at the time of their diagnosis including primary protocols UKALL11, UKALL 97/99, and UKALL2003 for ALL [19-21]; AML10 and AML12 for AML [22, 23]; and relapse protocols R1, R2, and R3 for ALL [24-26]. Protocols for ALL consisted of complex regimens of high but variable doses of steroids with prednisolone and/or dexamethasone [19-21, 24-26].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] The Pediatric Oncology Group (POG, now part of the Children's Oncology Group, COG) investigated six to 12 infusions of intermediate-dose intravenous (i.v.) MTX (1 g/M 2 ) followed by leucovorin rescue at 2-3 week intervals (IDMTX).…”
Section: Introductionmentioning
confidence: 99%